2022
DOI: 10.31234/osf.io/9cv8f
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Co-production to understand on-line help-seeking for young people experiencing emotional abuse and neglect: building capabilities, adapting research methodology, evaluating involvement and impact

Abstract: Background: Involving young people (YP) as co-researchers (YCoR) in mental health research is important for ethical and epistemological reasons. However, approaches to involve and evaluate ‘meaningful involvement’ in complex qualitative mental health research, and how to evaluate impacts (or change) for the co-researcher and the research is less well defined. Objectives: The co-produced research explored experiences of YP seeking help for emotional abuse and neglect via an on-line, peer-peer message board. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Critical contextual and psychological evidence from the interpretative phenomenological co-analysis reported in detail in Bennett et al ( 2022) 19 informed the co-produced thematic and conversation analyses reported here embedding YCoRs lived experience throughout the study. 19,34…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Critical contextual and psychological evidence from the interpretative phenomenological co-analysis reported in detail in Bennett et al ( 2022) 19 informed the co-produced thematic and conversation analyses reported here embedding YCoRs lived experience throughout the study. 19,34…”
Section: Discussionmentioning
confidence: 99%
“…Full details of the YCoR recruitment, characteristics and co-production involvement methodology is detailed elsewhere. 34 In summary, 10 YCoR from the NeurOX Young people's Advisory Group (YPAG; in the Neuroscience, Ethics and Society Group in the Department of Psychiatry and University of Oxford), some of whom had used the service, were enlisted to the research project team and followed the group's agreed principles of co-production and terms of reference. 35 NVivo (v12) qualitative software was used by one of the adult researchers (VB) to annotate and code extracts of the text and organise identified themes as they were discovered; data was exported to Excel to share with YCoR.…”
Section: Involvement Of Ycor In the Co-design Of Methodologymentioning
confidence: 99%
See 2 more Smart Citations